Impact on the reach of organic Facebook advertising to increase sales in "Novedades Jimber" Leónidas Plaza - Valencia Cedeño, Pablo (2023)
Entrepreneurships under post-covid19 conditions have developed new digital marketing strategies to position themselves in the local and regional market. The present study pursued the objective of implementing organic Facebook advertising strategies to increase sales in "Novedades Jimber" Leónidas Plaza. A methodology directed in two stages was used, the first consisted of diagnosing the level of the enterprise and competitors; The second stage was structured to develop advertising based on the geographical scope, the objectives and the means of dissemination, paying tribute to a mixed inquiry consisting of collecting, analyzing and integrating both quantitative and qualitative research. The method used was the descriptive analytic that made it easier to determine the effectiveness of advertising on social networks. The study population is the customers who frequent the business through a simple non-probabilistic random sampling for convenience, with a sample of 37 customers. Among the most representative results is that 45.7% have learned about the venture through the recommendations of other clients and 95.5% are unaware of the existence of a business fan page to establish online purchases. The reliability of the instrument was 0.85 Cronbach's alpha, recognizing it as good. The development of advertising based on the venture has brought an increase in sales and better relationship management with its customers and consumers.